The impact of export promotion programme towards enhancing Malaysia’s export performance: the case of Malaysia External Trade Development Corporation (MATRADE) / Nur Hidayati Zakaria - Zakaria, Nur Hidayati (Faculty of Business and Management, 2010)
This report is aim to investigate whether the export promotion activities as MATRADE core functions is indeed effective and bring benefit towards Malaysian exporters or not. MATRADE as government agency will provide the institutional support and also financial support in the form of grants. This report is also aim to find out whether the grants provided by MATRADE is efficient in encouraging Malaysian exporters to aggressively develop and market Malaysian products and services to the world. The study will look at events that MATRADE organize or facilitate and also the grants that being offered such as Market Development Grant and Brand Promotion Grant. The data will be collected from MATRADE Annual Report, MATRADE portal and through interview with some of the exporters. The information that gathers and findings will be used to improve the performance and effectiveness of MATRADE roles in helping Malaysian exporters to expand their products and services in international market and thus enhancing Malaysia’s export performance.